Rhegmatogenous Retinal Detachment Associated with Choroidal Detachment - L. Sh. Bilandarli (Oftalʹmologiâ, 2017)
Review describes the theme of rhegmatogenous retinal dеtаchment associated with choroidal separation. It is rare, but quite severe eye pathology. In most cases it has a very poor prognosis. Most authors consider the retinal detachment as a primary pathogenetic part, which decompensates the production of aqueous humor by increasing the absorptive surface of the retinal pigment epithelium. Dilatation of choroidal arterioles occurs in hypotension, it leads to extravasation of protein-rich fluid in the choroidal and the suprachoroidal space. This helps to further swelling and separation of the ciliary body and the choroid with reduced production of aqueous humor and progressive hypotension. There is a high risk of developing “retino-choroidal” separation in patients with macular rupture due to localization of retinal separation and rupture rear hyaloid membrane. The protein level in aqueous humor can be increased to 70 times. It may be a result of reflux of suprachoroidal proteins through uveoscleral route and / or venous proteins through the trabecular network. In addition, the diffusion of proteins from the posterior camera and vitreous cavity is possible. This creates favorable conditions for cell proliferation that can lead to postoperative proliferative vitreoretinopathy. Typically patients have a pronounced signs of inflammation, pain, and “red eye”, which is accompanied with vision decrement. Rhegmatogenous retinal reparationcan be associated with such clinical symptoms as severe panuveit, deepening of the anterior camera and the inflammatory response in the moisture, concentric wrinkles and sagging back of the iris, posterior synechia, iridofakodenez, blurred vitreous detachment of the ciliary body, hypotension, and choroidal and retinal detachment in addition. Debatableness of etiopathogenesis and a clinical picture, which is similar to other eye diseases create significant difficulties in early diagnosis and proper treatment of this pathology. Correct early diagnosis of “retino-choroidal dеtаchment” is complicated by several factors: sluggish pupil dilation, exacerbated by the presence of posterior synechiaes, clouding environments with the presence of cellular elements, choroidal dеtаchment, masking the retinal tears. Rhegmatogenous retino–choridal dеtаchment should be differentiated from a number of pathologies. The most obvious sign of “retinyl choroidal” dеtаchment is severe generalized inflammation leading to an erroneous diagnosis of uveitis. A particular problem is the differentiation with syndrome of uveal effusion, choroidal melanoma. Retino-choroidal dеtаchment is a rare pathology that requires timely and correct diagnosis of pathogenically based treatment.